Clinical Guide to Early Interventions for Children with Autism - Vivanti, Giacomo; Bottema-Beutel, Kristen; Turner-Brown, Lauren; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book examines early interventions for children with autism spectrum disorder (ASD) with the goal to enable primary care physicians as well as other clinicians, therapists, and practitioners to assist parents in making informed decisions based on current research. It provides a map for successfully navigating the maze of early interventions for ASD, focusing on evidence. Chapters review the similarities and differences between current evidence-based treatments, how these treatments work, the factors that facilitate their effectiveness, and the pros and cons of their use for different children and different needs. In addition, chapters discuss the services, laws, policies, and societal issues related to early intervention in ASD. Featured topics include: Criteria to evaluate evidence in ASD interventions. Effective approaches for Social communication difficulties in ASD. Effective approaches for Restricted and repetitive behaviors (RRBs) in ASD. Naturalistic, developmental approaches to early intervention for children with ASD The TEACCH approach and other visually based approaches for children with ASD. Applied Behavior Analysis (ABA) approaches to early intervention for children with ASD. What works for whom in ASD early intervention Clinical Guide to Early Interventions for Children with Autism is an essential resource for clinicians, primary care providers, and other practitioners as well as researchers, professors, and graduate students in the fields of child, school, and developmental psychology, pediatrics, social work, child and adolescent psychiatry, primary care medicine, and related disciplines.
Chapter 1. Autism and Autism Treatment: Evolution of Concepts and Practices from Kanner to Contemporary Approaches -- Chapter 2. Criteria to Evaluate Evidence in Interventions for Children with Autism -- Chapter 3. Understanding and Addressing Social Communication Difficulties in Children with Autism -- Chapter 4. Understanding and Addressing Restricted and Repetitive Behaviors in Children with Autism -- Chapter 5. Applied Behavior Analytic Approaches to Early Intervention for Children with Autism -- Chapter 6. Naturalistic Developmental Behavioral Interventions for Children with Autism -- Chapter 7. The TEACCH Approach and other Visually Based Approaches for Children with Autism -- Chapter 8. Choosing the (3z(BRight(3y (BProgram for Each Child in Autism Early Intervention -- Chapter 9. Beyond Monolithic Packages: Important Strategies Across Early Interventions for Children with Autism -- Chapter 10. Understanding Legislation, Health Insurance, and Disparities in Service Provision in Autism Early Intervention. .s
Keywords: Child psychology; School psychology; Pediatrics; Social work; Developmental psychology; Child psychiatry; Child and School Psychology; Pediatrics; Social Work; Developmental Psychology; Child and Adolescent Psychiatry